1979
DOI: 10.1103/physrevlett.43.1395
|View full text |Cite
|
Sign up to set email alerts
|

Stability Study of High-βFlux-Conserving Equilibria

Abstract: The flux-conserving tokamak model suggested that rapid heating would yield equilibria with high relative energy density {(3 = 2p/B 2 ) while nonetheless allowing control over q> the so-called safety factor for instability within the ideal magnetohydrodynamic plasma model. In this study, we show that this is adequate to provide stability to /3 values of 10%, if there is a superconducting metal shell in the vicinity of the plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

1981
1981
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 8 publications
1
30
1
Order By: Relevance
“…(5.171), a number of numerical codes have been developed for testing ballooning mode stability (Dobrott et al , 1979;Miller and Moore, 1979;Charlton et al , 1979;Todd et al , 1979;Bernard et al , 1980). Such studies show that by optimizing profiles and cross sections, one can obtain critical (P)'s on the order of 5 -10%.…”
Section: Internal Modes (Localized: Nlercier Criterion)mentioning
confidence: 99%
See 3 more Smart Citations
“…(5.171), a number of numerical codes have been developed for testing ballooning mode stability (Dobrott et al , 1979;Miller and Moore, 1979;Charlton et al , 1979;Todd et al , 1979;Bernard et al , 1980). Such studies show that by optimizing profiles and cross sections, one can obtain critical (P)'s on the order of 5 -10%.…”
Section: Internal Modes (Localized: Nlercier Criterion)mentioning
confidence: 99%
“…, Charlton et al , 1979;Todd et al , 1979), studies have shown that the (p) limits for arbitrary internal modes are most stringent for the n~ao ballooning modes. However, modes with such a fine-scale structure are likely to be affected by other physics (e.g.…”
Section: Internal Modes (Localized: Nlercier Criterion)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, in practice, mode resolution and hence computer memory requirements restrict the analysis to n ( 10. The ballooning theory has been modified to include finite-n corrections, and has been shown to agree with the detailed MHD approach down to n -5 [16][17][18]. Ballooning theory predicts that the largest n modes are the most unstable, and that as n is decreased the growth rate decreases monotonically.…”
Section: Introductionmentioning
confidence: 99%